The future world of agriculture - Murphy, Wendy B.; Grolier Incorporated (USA : Walt Disney Productions, 1984)
Traces the history of agriculture with emphasis on future methods of farming and growing food.
Based on the Land exhibit at Walt Disney's EPCOT Center.
Includes index.
Keywords: Agricultural exhibitions -- Florida; Agricultural exhibitions -- Florida -- Juvenile literature; Agricultural innovations; Agricultural innovations -- Exhibitions -- Juvenile literature; Agricultural innovations -- Juvenile literature; Agriculture -- History; Agriculture -- History -- Exhibitions -- Juvenile literature; Agriculture -- History -- Juvenile literature; EPCOT Center (Fla.); EPCOT Center (Fla.) -- Juvenile literature